Heterochromatin protein 1 (HP1) modulates replication timing of the Drosophila genome - Schwaiger, Michaela; Kohler, Hubertus; Oakeley, Edward J.; Stadler, Michael B.; Schübeler, Dirk (Genome Research, 2010)
The replication of a chromosomal region during S phase can be highly dynamic between cell types that differ in transcriptome and epigenome. Early replication timing has been positively correlated with several histone modifications that occur at active genes, while repressive histone modifications mark late replicating regions. This raises the question if chromatin modulates the initiating events of replication. To gain insights into this question, we have studied the function of heterochromatin protein 1 (HP1), which is a reader of repressive methylation at histone H3 lysine 9, in genome-wide organization of replication. Cells with reduced levels of HP1 show an advanced replication timing of centromeric repeats in agreement with the model that repressive chromatin mediates the very late replication of large clusters of constitutive heterochromatin. Surprisingly, however, regions with high levels of interspersed repeats on the chromosomal arms, in particular on chromosome 4 and in pericentromeric regions of chromosome 2, behave differently. Here, loss of HP1 results in delayed replication. The fact that these regions are bound by HP1 suggests a direct effect. Thus while HP1 mediates very late replication of centromeric DNA, it is also required for early replication of euchromatic regions with high levels of repeats. This observation of opposing functions of HP1 suggests a model where HP1-mediated repeat inactivation or replication complex loading on the chromosome arms is required for proper activation of origins of replication that fire early. At the same time, HP1-mediated repression at constitutive heterochromatin is required to ensure replication of centromeric repeats at the end of S phase.
10.1101/gr.101790.109